A Review of Flood Mitigation Literature: A Case Study of Sidoarjo Regency, Indonesia - Koerniawan, Fifiet; Setiawan, Muhammad Ikhsan; Laksito, Grida Saktian (Indonesia Academia Research Society, 2023)
Sidoarjo is a buffer city in Surabaya and is a comfortable and livable city. To become a livable city, a city needs several life-supporting infrastructures, including drainage infrastructure. A drainage system that is managed and maintained properly can carry out its functions optimally. But of course, many housing developments do not pay attention to the drainage system, which can cause problems such as flooding. Floods are the most frequent natural disasters in Indonesia. Flooding is a situation where an area is inundated with large amounts of water. The occurrence of floods can be predicted by paying attention to the amount of rainfall and water discharge. However, strong winds or leaking embankments can cause sudden floods which are usually called flash floods. The causes of flooding include heavy rain. The earth's surface is lower than sea level. This area is a delta which has low water absorption capacity. Construction of buildings along riverbanks. The river flow is uneven because it is blocked by rubbish and lack of land cover in upstream areas. Even if you live in a flood-free area, everyone should be aware of the potential for this natural disaster. Floods are the release of river water that is relatively larger than usual, resulting in overflowing river water that fills and inundates low-lying areas.